LES study of influence of obstacles on turbulent premixed flames in a small scale vented chamber - Sreenivasa Rao Gubba; Salah S. Ibrahim; W. Malalasekera (2009)
The LES study reported in this paper presents the influence of number and position of the obstacles on turbulent premixed flames. LES simulations have been carried out for a stagnant, stoichiometric propane/air mixture, ignited from rest in a small laboratory scale, vented chamber, capable of rearranging into various configurations based on number and position of baffle plates. The novelty of the present study is two folded. First is the application of novel dynamic flame surface density (DFSD) model to account the sub-grid scale (SGS) chemical reaction rate in LES. Second is the arrangement of these configurations into four families, which facilitate a qualitative comparison with available experimental measurements. The concept of families also offers to understand the flame-flow interactions and the impact of number and position of the baffles with respect to ignition origin.